Analisis Wacana Kritis Adopsi Bahasa Asing dalam Al-Quran dalam Buku Arthur Jeffery (The Foreign Vocabulary of The Quran) - Ismi Wakhidatul Hikmah; Lianfin Safira Aulia (Jalsah : The Journal of Al-quran and As-sunnah Studies, 2022)
Arthur Jeffery in his book The Foreign Vocabulary of The Quran states that there are non-Arabic language (foreign languages) in the Qur'an. This raises doubts about the authenticity of the language of the Koran wherein the Koran itself says that the language of the Koran in Arabic. This study uses critical discourse analysis promoted by Norman Fairclough where this theory focuses on how language is formed and shaped from social relations and certain contexts with three dimensions of Fairclough's critical discourse analysis, namely text (text dimension), discourse practice (discursive practice), and sociocultural practice (socio-cultural practice). The results of this study are doubts about the authenticity of the language of the Qur'an were broken by Muslim scholars and Arthur Jeffery's opinion that the existence of a foreign language in the Qur'an has clearly been proven wrong with the available data from Muslim scholars. Therefore, we conclude that the language of the Qur'an is Arabic